Development of Japanese Language Learning Application with Word Tracing Approach - Tee, Mei Hui; Othman, Muhammad Fakri (Applied Information Technology And Computer Science, 2023)
Foreign language learning has grown in importance in Malaysian higher education due to the globalisation, industrialization, and economic needs. The Japanese language is both popular and challenging foreign languages to learn. The existing applications to learn Japanese language that have been researched are lack of word tracing implementation and lack of multimedia elements such as graphics and audios. Therefore, this project is aimed to develop a Japanese language mobile learning application named Japanese Diary implementing word tracing approach based on Multimedia Mobile Content Development (MMCD) methodology. This project’s target users are Universiti Tun Hussein Onn Malaysia (UTHM) students aged 18 to 25. Positive findings with an average of 89.13% were obtained through user acceptance testing based on Technology Acceptance Model (TAM). This application is expected to assist students learn the fundamentals of Japanese through lesson and quiz modules, and a katakana syllabus for word tracing is suggested for future development.